2018
DOI: 10.18203/2319-2003.ijbcp20181631
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of used eye drop containers for microbial contamination in outpatient department of tertiary care teaching hospital

Abstract: Background: Contaminated eyedrops are considered as serious risk factor for many iatrogenic ocular infections. Apart from the risk of infection, microbial contamination may alter the pH of the solution thereby reducing the efficacy of drugs. Presently many preservatives are added to these eye drops preparations to extend the duration of use. Hence authors aimed this study to find the contamination rates in such eye drop preparations.Methods: This was a prospective observational research conducted at Ophthalmol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…In fact, the eye drops's shelf-life is determined by the preservatives themselves, rather than the main components. Expired eyedrop mean loss of preservative potency to protect the eye drops from microbial contamination [42]. Therefore, preservatives must fulfill certain requirement such as; compatibility with other components in the eye drops, non-toxic and must be efficient during the entire of use.…”
Section: Efficacy Testmentioning
confidence: 99%
“…In fact, the eye drops's shelf-life is determined by the preservatives themselves, rather than the main components. Expired eyedrop mean loss of preservative potency to protect the eye drops from microbial contamination [42]. Therefore, preservatives must fulfill certain requirement such as; compatibility with other components in the eye drops, non-toxic and must be efficient during the entire of use.…”
Section: Efficacy Testmentioning
confidence: 99%
“…The sterility of eye drops should be, ideally, secured throughout the manufacturing process and the supply chain and maintained for the recommended duration of use, from opening to handling by the end user [ 10 , 11 ]. A literature review showed that the microbial contamination rate of preserved and preservative-free eye drops varied from 2.3 to 73% [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. The most important point was that fungal and bacterial microorganisms were cultured from the dropper tip, cap, and contents of eye drops [ 20 , 22 , 26 , 39 , 43 , 46 ,…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria from the human commensal flora were the predominant isolated microorganisms [ 17 , 18 , 21 , 22 , 26 , 30 , 34 , 41 , 43 , 46 , 49 ], logically, since the contamination occurred after the bottle was opened. Limited growth of pathogenic bacteria and airborne environmental bacterial and fungal spores were also reported [ 15 , 24 , 29 , 34 , 43 , 50 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations